ANALISIS LINGKUNGAN INTERNAL DAN EKSTERNAL DI LEMBAGA PENDIDIKAN ISLAM DALAM MENGHADAPI ERA DISRUPSI - Yahya, Muhammad (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
The aim of this research is to describe strengthening the analysis of the internal and external environment of SDI Darul Muttaqin in facing the era of disruption, so that it continues to survive. The method used in this research is a qualitative descriptive method. Data collection techniques used semi-structured interviews, semi-participant observation, and documentation. The analysis techniques used include data collection, data condensation, data presentation, and data conclusion. The results of this research show: 1) analysis of the internal environment of SDI Darul Muttaqin consisting of competency aspects in the form of good quality educational institutions, core competencies in the form of SDI Darul Muttaqin's contribution to the Gresik Regency Government by sending its students to competitions, the resource aspect which is dominated by teachers with undergraduate graduates, 2) analysis of the external environment, namely SDI Darul Muttaqin always tries to collaborate with existing stakeholders, collaborate with external organizations, the role and support of the local government for SDI Darul Muttaqin in increasing school quality competition, 3) efforts to strengthen the internal environment are carried out by SDI Darul Muttaqin by utilizing digital-based learning media, each educator is given insight into the use of technology, communicating with guardians who use smartphone media, 4) strengthening the external environment is carried out by holding regular outreach with the community and stakeholders, the use of technology in facilities and infrastructure used. This strengthening effort is carried out to prepare students to be able to face the era of disruption.